Toddler Posyandu Cadres Supporting Stunting-Free Villages - Sandra, Feni; Choiriyah, Ilmi Usrotin (Indonesian Journal of Cultural and Community Development, 2024)
Background: Posyandu (integrated health service posts) are vital for maternal and child health. Specific Background: This study explores the role of Posyandu cadres in health promotion and community empowerment in a local village. Knowledge Gap: Previous research has highlighted the importance of these cadres, but their contributions to community mobilization and stunting prevention remain underexplored. Aims: The research aims to examine the functions of Posyandu cadres in health education and community engagement. Results: Findings indicate that cadres act primarily as health educators and community mobilizers, utilizing tools like the KIA (Child Identity Card) and KMS (Healthy Growth Monitoring Card) for health information dissemination. However, their active involvement and local capacity-building efforts need improvement. Novelty: This study offers new insights into the operational challenges faced by Posyandu cadres in promoting health and preventing stunting. Implications: It emphasizes the need for training and support for cadres to enhance their effectiveness, ultimately contributing to healthier communities and reducing stunting rates. Highlights : Roles of Cadres: Primarily function as health educators and community mobilizers. Utilization of Tools: Employ KIA and KMS for effective health information dissemination. Need for Improvement: Highlight the necessity for enhanced training and active community involvement. Keywords: Posyandu, health promotion, community empowerment, stunting prevention, cadres.